Analisis Penerapan Akad Mukhabarah Pada Koperasi Sawit Lagan Jaya di Kabupaten Tanjung Jabung Timur - M. Mukhlis Darmawan; Habriyanto Habriyanto; Agusriandi Agusriandi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the implementation of the mukhabarah agreement at the Lagan Jaya Palm Oil Cooperative in East Tanjung Jabung Regency, specifically in its collaboration with PT Indonusa Agromulya as a partner company. The mukhabarah agreement, which in local practice is better known as a cooperation agreement, is a form of profit-sharing agreement between landowners and managers. In this study, the focus is directed at how the agreement is implemented, the extent to which it complies with sharia principles, and the obstacles that arise in practice in the field. The type of research used is qualitative research with a case study approach. Primary data was obtained through in-depth interviews with cooperative administrators, plasma farmers, and related parties, while secondary data was obtained from cooperation agreement documents (SPK), profit-sharing reports, and literature related to the mukhabarah agreement. Data collection techniques were conducted through interviews, observation, and documentation. Data analysis used the methods of reduction, presentation, and inductive drawing of conclusions. The results of the study indicate that the implementation of a written mukhabarah contract has fulfilled the basic principles of sharia, namely the clarity of the rights and obligations of each party, as well as a profit-sharing system with a 50:50 ratio. However, in practice, several obstacles were found, including weak company management in plantation maintenance, delays and inconsistencies in profit sharing, and minimal supervision from the cooperative and the involvement of plasma farmers. These factors cause a misalignment between the contents of the contract and the reality, thus harming the cooperative and plasma farmer members. This study confirms that the success of a mukhabarah contract is not only determined by the written agreement, but also by the consistency of implementation, transparency in profit sharing, and collective supervision from all parties involved. These findings are expected to provide a practical contribution to cooperatives in improving cooperation systems, as well as become academic considerations for Islamic economic studies related to the implementation of the mukhabarah contract in the plantation sector